Mitochondrial Targeting and pH-Responsive Nanogels for Co-Delivery of Lonidamine and Paclitaxel to Conquer Drug Resistance - Chen, Enping; Wang, Ting; Zhang, Junmei; Zhou, Xiang; Niu, Yafan; Liu, Fu; Zhong, Yinan; Huang, Dechun; Chen, Wei (Frontiers in Bioengineering and Biotechnology, 2021)
Multidrug resistance (MDR) is one of the leading causes for the failure of cancer chemotherapy and mainly attributed to the overexpression of drug efflux transporters in cancer cells which is dependent on adenosine triphosphate (ATP). To overcome this phenomenon, herein a mitochondria-directed pH-sensitive polyvinyl alcohol (PVA) nanogel incorporating the hexokinase inhibitor of lonidamine (LND) and the chemotherapeutic drug of paclitaxel (PTX) was developed to restore the activity of PTX and synergistically treat drug resistant tumors. The introduction of 2-dimethylaminoethanethiol (DMA) moiety into the nanogels not only promoted the drug loading capacity, but also enabled the lysosomal escape of the nanogels. The subsequent mitochondria targeting facilitated the accumulation and acid-triggered payload release in the mitochondria. The released LND can destroy the mitochondria by exhausting the mitochondrial membrane potential (MMP), generating the reactive oxygen species (ROS) and restraining the energy supply, resulting in apoptosis and susceptibility to PTX of the MCF-7/MDR cells. Hence, the nanogel-enabled combination regimen of LND and PTX showed a boosted anti-tumor efficacy in MCF-7/MDR cells. These mitochondria-directed pH-sensitive PVA nanogels incorporating both of PTX and LND represents a new nanoplatform for MDR reversal and enhanced therapeutic efficacy.